2017
DOI: 10.1002/etc.3933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo exposure to 3,3′,4,4′‐tetrachlorobiphenyl (PCB 77) on heart development in tree swallow (Tachycineta bicolor)

Abstract: Tree swallow (Tachycineta bicolor) eggs from 2 uncontaminated sites, the Patuxent Research Refuge (Laurel, MD, USA) and the Cobleskill Reservoir (Cobleskill, NY, USA) were dosed with polychlorinated biphenyl (PCB) 77 to evaluate effects on the developing cardiovascular system. To ensure embryonic viability, treatments were administered into the air cell at embryonic day 2.5 including: untreated (control), vehicle (filtered sterilized fatty acid mixture), 100 ng/g and 1000 ng/g egg. Eggs were dosed in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Given the lack of a dose‐response relationship for mortality over the doses tested for PCB 77, any effects of exposure would likely be more subtle changes in biochemistry and physiology. These findings are consistent with our previous data in tree swallows in which embryonic exposure to PCB 77 did not impact mortality; however, there was greater incidence of cardiomyopathies (Carro et al ). It is interesting to note that despite the lack of an apparent dose‐response relationship for mortality for PCB 77, the quantifiable increase in mortality is similar to mortality increases above controls for the lowest doses of the other 3 treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Given the lack of a dose‐response relationship for mortality over the doses tested for PCB 77, any effects of exposure would likely be more subtle changes in biochemistry and physiology. These findings are consistent with our previous data in tree swallows in which embryonic exposure to PCB 77 did not impact mortality; however, there was greater incidence of cardiomyopathies (Carro et al ). It is interesting to note that despite the lack of an apparent dose‐response relationship for mortality for PCB 77, the quantifiable increase in mortality is similar to mortality increases above controls for the lowest doses of the other 3 treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Krautwald-Junghanns et al (12) found dilation or hypertrophy of the ventricular myocardium in 15% of 107 psittacine birds evaluated. On the other hand, cardiomyopathies in passerine birds have not been reported to date, and heart diseases reported in this group are restricted to congenital heart malformations caused by environmental exposure to polychlorinated biphenyls during embryonic development, which results in alterations in the size and shape of the heart (2,4).…”
Section: Discussionmentioning
confidence: 86%
“…Environmental factors are also a consideration. A study into the effects of polychlorinated biphenyl (PCB) 77 showed that in the tree swallow (Tachycineta bicolor) in ovo exposure to the chemical results in higher levels of cardiomyopathy and ventricular wall abnormalities [83]. Age also had an effect on normal broiler roosters in comparison to mature roosters.…”
Section: Cardiomyopathiesmentioning
confidence: 99%